Comic strips help children understand medical research. Issue 4 (April 2015) - Grootens-Wiegers, Petronella; de Vries, Martine C.; van Beusekom, Mara M.; van Dijck, Laura; van den Broek, Jos M.
Highlights A comic strip on research was made with children to improve research information. The new material led to high levels of understanding and user satisfaction. Children were excited to participate and that they 'could be a part of science'. The children offered valuable insights that we could not have achieved without them.